EVALUATION OF ANTI-ANXIETY ACTIVITY OF SILICA GEL ENTRAPPED TRADITIONAL MEDICINE - Bhattacharyya, Lopamudra (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objectives: The present study has been designed to compare the anxiolytic property of Makaradhwaja (a well-known traditional Ayurvedic medicine) and gel encapsulated Makaradhwaja in laboratory animals. Methods: Makaradhwaja has been encapsulated into silica gel matrix to enhance the bioavailability and potency. The proper formation of the gel has been evidenced by the transmission electron microscopy micrograph and Fourier transform infrared (FTIR) spectrometry. Due to the presence of Makaradhwaja into silica gel matrix broad peaks at 3474 cmâ€“1 and 1637 cmâ€“1 were detected in FTIR spectrum. The UV-visible spectroscopic analysis reveals sustainable and controlled release (up to 50%) of the drug for more than 240 hrs. The anti-anxiety activity was studied by exposing the mice into two different anti-anxiety models like elevated plus maze (EPM) and actophotometer. Results: The gel encapsulated Makaradhwaja has shown more potent anxiolytic effect than the crude Makaradhwaja in the EPM (significant increase in the number of entries and time spent in the open arm). The number of locomotor score in actophotometer has also been significantly increased by the gel encapsulated Makaradhwaja. Conclusion: Present study confirms that the gel encapsulated Makaradhwaja has significant anxiolytic activity which is comparable with standard anxiolytic diazepam. Keywords: Actophotometer, Makaradhwaja, Elevated plus maze.